Distribution of Labor Absorption in the Inisiatif Lampung Sehat Non-Governmental Organization (NGO) Across Regencies/Cities in Lampung Province, 2025 - Dwi Setyorini; Ida Budiaty DA; I Wayan Suparta (CV. Bimbingan Belajar Assyfa, 2026)
Public health development at the regional level requires the involvement of various stakeholders, including non-governmental organizations (NGOs) as strategic partners of the government in reaching vulnerable communities. This study aims to analyze the distribution of labor absorption and the effectiveness of program output achievements in Tuberculosis (TB) patient recovery programs implemented by the Inisiatif Lampung Sehat in Lampung Province. The study employed a descriptive approach utilizing both primary and secondary data related to the number of staff, volunteers, and TB patient recovery rates in 2025 across several regencies/cities within the intervention areas. The program output achievements demonstrated significant variations among regions, with several areas attaining very high recovery rates, even exceeding the established targets. However, the findings indicate that the number of workers is not always directly proportional to program success. Instead, program effectiveness is influenced by several factors, including the quality of implementation, workforce capacity, as well as social conditions and supporting systems in each region. The study concludes that the effectiveness of TB control programs is determined not only by the quantity of labor but also by proportional workforce distribution, the competency of field personnel, and the strength of integrated support systems. Therefore, a more adaptive and region-based human resource management strategy is required to improve program achievements in an equitable and sustainable manner.